Dynamics of Spirulina in Promoting Health Benefits for Arsenicosis Patients - Rahman, Muhammad Hasibur; Islam, AZM Maidul; Sikder, MS (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A total number of 40 patients affected with arsenicosis were selected and clinically examined prior to feeding trials. The interrelatedness between improvement respondents following spirulina intake in respect of age, sex, nutrition and social condition of patients exposed to arsenic contaminated water was evidenced. Among sexwise respondents about 62% females showed improvement in comparison to 58.3% males. The spirulina intake caused more improvements in age group 15-35 years (66.66%) than patients of 35 to 55 years (50%). The impact of spirulina improvement showed a different vulnerability of social taboos. It occurred 71.42% in middle class, while in poor class this was 69.29%. The greatly vulnerable poverty related malnourished arsenicosis patients responded to therapy equally as attained by well nourished patients. The overall response revealed that 60% patients showed improvement with spirulina treatment which was statistically highly significant (x2 = 8.64 at P< 0.01). The viability of spirulina to offer health benefits to arsenicosis patients proved considerably satisfactory, because there was significant improvements of general health in all patients who received spirulina during the experimental period. Although 60 to 70% recovery has been recorded with spirulina intake in arsenicosis patients, but it is still interesting to note that the drug assisted remedy from malnutrition and might have boosted up the immune system. The present research study evidenced that arsenic, which induces cellular toxicity, could be prevented by treatment with known supportive treatment, such as spirulina along with other antioxidants. DOI: 10.3329/jbcps.v26i1.4228 J Bangladesh Coll Phys Surg 2008; 26: 14-21